PENGUATAN SISTEM PRESIDENSIAL MELALUI PENERAPAN AMBANG BATAS PARLEMEN DALAM PEMILIHAN UMUM DI INDONESIA - Dihan Elzani; Dodi Haryono; Muhammad A. Rauf (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2023)
The parliamentary threshold is the minimum vote limit for political parties in generalelections to participate in determining the number of seats in the DPR. This parliamentarythreshold was created to stabilize the relationship between the Executive and the Legislature in ademocratic country. The aim of implementing the threshold provisions is to reduce the number ofpolitical parties in parliament in order to simplify the party system. Apart from that,parliamentary thresholds can also be used as an instrument to screen participants for the nextelection. In accordance with the mandate contained in the Constitutional Court's decisionNumber 52/PUU-X/2012, the parliamentary threshold only applies to calculating the valid votesobtained by political parties at the DPR level. Based on Law Number 7 of 2017, theparliamentary threshold for the 2019 election was again increased to a minimum of 4%.This legal research is normative legal research. Normative legal research is legalresearch carried out by examining library materials or secondary data and tertiary legalmaterials. This type of normative law is also called doctrinal legal research, also known aslibrary research or document study. It is called doctrinal legal research, because this research iscarried out or directed only at written regulations or other legal materials. Comparative legalresearch is research that finds and looks for differences in various legal systems.The conclusions that can be obtained from the research results are: First, the regulationregarding the parliamentary threshold in Indonesia continues to experience developmentstarting from the enactment of the 2009 Legislative Election at 2.5% Second, the parliamentarythreshold is a system that strengthens presidential government, because a multiparty system is aform of combination that is not compatible with a presidential government system. Indonesiashould adhere to the threshold system implemented by countries that have been successful inimplementing thresholds, such as Turkey,Keywords : Parliamentary Threshold, General Election, Presidential.